2014
DOI: 10.1007/s00276-014-1281-y
|View full text |Cite
|
Sign up to set email alerts
|

Is low tie ligation truly reproducible in colorectal cancer surgery? Anatomical study of the inferior mesenteric artery division branches

Abstract: The division branches of the IMA are extremely subject to interindividual variations, making it difficult if not impossible to reproduce identically a surgical procedure based on their anatomy. HT appears to us as the only relevant procedure for colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 19 publications
2
31
0
Order By: Relevance
“…These papers are difficult to compare because different classification [13]. In a series of 117 patients, Bertrand, et al used Zebrowski's classification, which consisted of eight types [1]. They observed a fan-shaped branching pattern in approximately 20 % of the cases, which is comparable to the 29 % we found in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These papers are difficult to compare because different classification [13]. In a series of 117 patients, Bertrand, et al used Zebrowski's classification, which consisted of eight types [1]. They observed a fan-shaped branching pattern in approximately 20 % of the cases, which is comparable to the 29 % we found in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…The use of the branching pattern of the LCA to evaluate the surgical difficulties of the LT technique has been investigated in a few studies [1,10]. These papers are difficult to compare because different classification [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This did not significantly increase total operating time. Some studies30 31 have reported that an IMA branching pattern with a large distance between the origins of the IMA and LCA causes technical difficulty. It would appear that surgeons should not hesitate to change the tie level of the IMA when performing a difficult low‐tie ligation.…”
Section: Discussionmentioning
confidence: 99%